2018
DOI: 10.3851/imp3183
|View full text |Cite
|
Sign up to set email alerts
|

The Ultra-Short Virological Dynamics in Response to Entecavir or Lamivudine during Chronic Hepatitis B with Spontaneous Severe Acute Exacerbation

Abstract: CHB with spontaneous SAE responded similarly to treatment using either LVD or ETV, with both drugs inducing a rapid decline of HBV viral load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…We were not able to evaluate the predictive role of dynamic changes in HBV DNA as the short term changes in HBV DNA were not routinely measured in clinical practice. Although a few studies found that viral kinetics can predict the severity of AE in patients with CHB[32], a recent study showed that in patients with spontaneous SAE of CHB, either lamivudine or entecavir could induce a rapid decline of HBV viral load[38]. Second, the patients in this study were admitted from January 2011 to August 2018; although all patients received standard conservative therapy upon admission, the treatment methods may be different among the patients with SAE before admission.…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to evaluate the predictive role of dynamic changes in HBV DNA as the short term changes in HBV DNA were not routinely measured in clinical practice. Although a few studies found that viral kinetics can predict the severity of AE in patients with CHB[32], a recent study showed that in patients with spontaneous SAE of CHB, either lamivudine or entecavir could induce a rapid decline of HBV viral load[38]. Second, the patients in this study were admitted from January 2011 to August 2018; although all patients received standard conservative therapy upon admission, the treatment methods may be different among the patients with SAE before admission.…”
Section: Discussionmentioning
confidence: 99%